2011
DOI: 10.1007/s10389-011-0403-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and impact of a meningococcal C conjugate vaccination program in 13- to 25-year-old individuals in Galicia, Spain

Abstract: BackgroundIn response to increased case numbers of meningococcal group C disease, catch-up vaccination strategies have been shown to be successful. This paper describes the results of a repeat vaccination program in Galicia, Spain, and the strategy used for it.Methods and resultsThree vaccination waves were performed: first, in 1996/1997 with a meningococcal group A and C polysaccharide vaccine in individuals aged 18 months to 19 years; second, in 2000 with a conjugate serogroup C polysaccharide vaccine in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A total of 30 studies reported impact of MCCV vaccination programs and 17 studies reported vaccine effectiveness (direct effect) of MCCV. Studies came from 9 different countries; 11 from England and Wales/UK [20][21][22][23][24][25][26][27][28][29][30], 10 from Spain [31][32][33][34][35][36][37][38][39][40], 5 from Canada [41][42][43][44][45], 4 each from Brazil [46][47][48][49] and Italy [50][51][52][53], 2 each from Australia [54,55] and the Netherlands [56,57], and one each from Germany [58] and Belgium [59]. The MCCV were introduced as part of the routine childhood NIP in all these countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 30 studies reported impact of MCCV vaccination programs and 17 studies reported vaccine effectiveness (direct effect) of MCCV. Studies came from 9 different countries; 11 from England and Wales/UK [20][21][22][23][24][25][26][27][28][29][30], 10 from Spain [31][32][33][34][35][36][37][38][39][40], 5 from Canada [41][42][43][44][45], 4 each from Brazil [46][47][48][49] and Italy [50][51][52][53], 2 each from Australia [54,55] and the Netherlands [56,57], and one each from Germany [58] and Belgium [59]. The MCCV were introduced as part of the routine childhood NIP in all these countries.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2008 the vaccine coverage has remained > 95% for infant and > 94% for the booster dose [ 32 ]. There was a total of 7 studies from Spain (3 national studies [ 31 33 ], and one study each for Navarra [ 34 ], Galicia [ 35 ], Andalusia [ 36 ] and Catalonia regions [ 37 ]). Regardless of studies and study periods, the largest decrease of MenC cases was observed in children, with a decrease of 90–100% and 88–100% in < 1 and 1–4 years old respectively.…”
Section: Resultsmentioning
confidence: 99%